Papillon [videorecording (Blu-Ray)] - Trumbo, Dalton, 1905-1976; Semple, Lorenzo; McQueen, Steve, 1930-1980; Hoffman, Dustin, 1937-; Jory, Victor, 1902-1982; Gordon, Don, 1926-2017; Zerbe, Anthony, 1936-; Charrière, Henri, 1906-1973 (Archive collection., 2018)
A criminal, sent to prison on Devil's Island, begins at once to engineer his escape in this portrayal of prison life.